Influence of social networking sites on scholarly communication: an altmetrics analysis of selected LIS journals / Bwsrang Basumatary ... [et al.] - Basumatary, Bwsrang; Boro, Bhaigyashree; Verma, Manoj Kumar; Mansor, Ahmad Nazri (Faculty of Information Management, 2022)
This study aims to examine the influence of social networking sites on scholarly papers published in Library and Information Science journals. Top 100 articles published in two renowned journals International Journal of Information Management and the Journal of Medical Library Association, that received high Altmetric Attention Score (AAS) have been taken for the study. The analysis found that LIS research is most often mentioned on Twitter, followed by news outlets and blogs. Student groups and librarians are among the most frequent readers of the publications. The Pearson correlation coefficient test revealed a very high and significant positive correlation between Scopus citation and Dimensions.ai citation, Mendeley readership and Scopus citation. However, AAS and Dimensions.ai citation is low correlation and statistically not significant. The findings indicate that journals need social media profiles to disseminate information among academia and society to increase online attention to LIS research.